Community gut colonization by tet(X4)-positive multidrug-resistant Escherichia coli in healthy individuals from urban residents in Shenzhen, China - Peng, Ruoyan; Liang, Pei; Jiang, Wenxiao; Li, Zhaodong; Wang, Li; Huang, Yi; Zhang, Xianfang; Guo, Yijia; Wang, Ying; Wang, Jing; Guo, Jiubiao; Yin, Feifei; et al. (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundTigecycline remains a last-resort antibiotic for treating multidrug-resistant (MDR) Gram-negative pathogens. The emergence of tet(X4)-mediated high-level tigecycline resistance in Escherichia coli has raised global concern, yet its prevalence in healthy human populations remains limited.MethodsWe conducted a community-based surveillance study involving 245 fecal samples from healthy individuals in three urban communities in Shenzhen, China. Tigecycine-resistant strains were isolated using MacConkey agar supplemented with 2 mg/L tigecycline and confirmed by PCR detection of tet(X). Antimicrobial susceptibility testing, whole-genome sequencing (WGS), and phylogenetic analysis were performed.ResultsTigecycline-resistant E. coli were detected in 1.6% (4/245) of samples. All isolates carried tet(X4) and exhibited an MDR phenotype. WGS revealed that tet(X4) was located on IncY (n=1) and IncFIA8-IncHI1/ST17 plasmids (n=3), which closely resembled previously described plasmids and co-harbored additional resistance genes. The core tet(X4)-carrying region in all four plasmids, associated with ISCR2, was highly similar to that of p47EC—the first tet(X4)-bearing plasmid identified in porcine E. coli in China. Notably, the three IncFIA-IncHI1/ST17 plasmids shared an identical 12,536-bp region structured as IS1–catD–tet(X4)–ISCR2–ΔISCR2–floR–ΔISCR2. Virulence-associated genes involved in adhesion, iron acquisition, biofilm formation, and secretion systems were also identified in four tet(X4)-positive isolates. The four isolates belonged to globally distributed sequence types ST10, ST201, ST877, and ST1308. Phylogenomic analysis demonstrated close genetic relatedness between these community isolates and strains from diverse geographical regions and hosts.ConclusionsThis study reveals silent intestinal colonization by tet(X4)-positive MDR E. coli among healthy urban residents, highlighting the role of community reservoirs in the dissemination of last-resort antibiotic resistance. These findings underscore the urgent need for One Health-oriented antimicrobial resistance surveillance and intervention strategies that extend beyond clinical settings.